(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this brief article it is argued that the ethical dimension, which is fundamental to Grotowski’s methodology, results from the radicalization of the simplest rules of professional decorum that are taught in drama schools and put into practice by most theater companies. This aspect is of extreme relevance, in the performing arts as in its pedagogy, when the dialectic between “work on oneself” and otherness is considered. Briefly, it is outlined Grotowski’s artistic path, to argue an ontological dimension of his notion of Art and to demonstrate its coherence and linearity. Also concisely, are indicated his main ethical and professional references and how these were applied into practice, highlighting the importance given to the Other. To finish, it is claimed the ethics as a professional and artistic imperative in the grotowskian context, grounding it in the professional decorum and the artistic practice.